2006
DOI: 10.1017/s1121189x00004450
|View full text |Cite
|
Sign up to set email alerts
|

The descriptive epidemiology of suicide in Tuscany, 1988-2002

Abstract: The cluster of excessive mortality from suicide in Southern Tuscany could be the consequence of social determinants, related to the urban and social crisis following agriculture decline and mine closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The former may be seen as largely responsible for the variation in social conditions that foster different national suicide rates, while the variation in the latter explain why a particular individual will succumb to suicide whereas others in broadly similar circumstances will not [21]. Suicide risk factors at the regional level include, for example, levels of economic deprivation and social fragmentation [22][23][24], societal integration [25,26], isolation (low population density and high proportions of households with only one member) [27], unemployment [27,28], state public welfare expenditures [29], urban/rural proportions [30][31][32], and access to health care [33,34]. All of these variables have been found to be associated with suicide and self-injurious behavior in high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…The former may be seen as largely responsible for the variation in social conditions that foster different national suicide rates, while the variation in the latter explain why a particular individual will succumb to suicide whereas others in broadly similar circumstances will not [21]. Suicide risk factors at the regional level include, for example, levels of economic deprivation and social fragmentation [22][23][24], societal integration [25,26], isolation (low population density and high proportions of households with only one member) [27], unemployment [27,28], state public welfare expenditures [29], urban/rural proportions [30][31][32], and access to health care [33,34]. All of these variables have been found to be associated with suicide and self-injurious behavior in high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Deinstitutionalization, however, also seems to be associated with increased rates in deaths for causes considered ' behaviourally avoidable ' (i.e. preventable with adequate health promotion policies), such as cardiovascular and unnatural causes for both genders (Hansen et al 2001) and for suicide (Mortensen & Juel, 1993 ;Martiello et al 2006). Vreeland (2007) stated that the problem of increased morbidity and premature death in people with serious mental illness needed to be addressed with a transformation of the current mental health system and the integration of physical and mental health care, towards a system that uses a coordinated, multidisciplinary holistic approach.…”
Section: Introductionmentioning
confidence: 99%
“…Smoothed mortality suicide rates were obtained using empirical Bayes in Tuscany. 35 A comparison of fully Bayesian and empirical Bayes methods was done in estimation of disease rates in spatial temporal variations. 36 Rezaeian et al 37 suggested the use of smooth rates in case of instability and used non iterative empirical Bayes method.…”
Section: Discussionmentioning
confidence: 99%